Product multiplet branching in the O(1D) + H2-->OH(2Pi) + H reaction. - Alexander, M; Rackham, E; Manolopoulos, D (2004)
The statistical model of atom-diatom insertion reactions is combined with coupled-states capture theory and used to calculate product multiplet-resolved integral cross sections for the title reaction. This involves an ab initio determination of the four electronic potential energy surfaces that correlate with the products ((1,3)A(') and (1,3)A(")), and an accurate description of the electronic and spin-orbit couplings between them. The dependence of the resulting cross sections on the final-state rotational quantum number shows a statistical behavior similar to that observed in earlier studies of the reaction in which only the lowest ((1)A(')) potential was retained. In addition, however, the present calculations provide information on the branching between the OH((2)Pi) multiplet levels. Although the two spin-orbit manifolds are predicted to be equally populated, we find a strong propensity for the formation of the Pi(A(')) Lambda-doublet states. These two predictions confirm the experimental results of Butler, Wiesenfeld, Gericke, Brouard, and their co-workers. The nonstatistical population of the OH Lambda-doublet levels is a consequence of the bond breaking in the intermediate H(2)O complex and is preserved through the multiple curve crossings as the products separate. This exit-channel coupling is correctly described by the present theory.